DEVELOPING AUDIOBOOK TO TEACH LISTENING COMPREHENSION FOR ELEVENTH GRADERS OF SENIOR HIGH SCHOOL - Herlyanti, Putri; Suhartono, Luwandi; Sumarni, Sumarni (Universitas Tanjungpura, 2023)
The goal of this study was to develop an audiobook as course materialfor teaching and developing listening comprehension. This wasdevelopment research, and the materials were designed using theADDIE procedure. Despite this, just three phases of the research wereimplemented: analyzing, designing, and developing. The finishedproduct for teaching and learning listening comprehension was Let